Distance-construal relationship: Mediating role of perceived control and moderating role of locus of control - Huang, Hui-dan; Zhang, Qi (Frontiers in Psychology, 2023)
Construal level theory (CLT) has been supported and applied widely in social psychology. Yet, the mechanisms behind it remain unclear. The authors extend the existing literature by hypothesizing that perceived control mediates and locus of control moderates the effect of psychological distance on construal level. Four experimental studies were conducted. Results indicate that individuals perceive low (vs. high) situational control from psychological distance (vs. proximity) and resultant control perception influences their motivation in control pursuit, producing high (vs. low) construal level. Moreover, locus of control (i.e. one’s chronic control belief) affects individual’s motivation to pursue control and yields reversal of distance-construal relationship under external (vs. internal) locus of control as a result. Overall, this research firstly identifies perceived control as a closer predictor of construal level and the findings are expected to help with influencing human behavior by facilitating individuals’ construal level via control-related constructs.